Electrical impedance spectroscopy for the characterization of skin barrier in atopic dermatitis. Issue 10 (15th May 2021) - Rinaldi, Arturo O.; Korsfeldt, Angelica; Ward, Siobhan; Burla, Daniel; Dreher, Anita; Gautschi, Marja; Stolpe, Britta; Tan, Ge; Bersuch, Eugen; Melin, David; Askary Lord, Nima; Grant, Simon; et al.
Abstract: Background: Allergic disorders such as atopic dermatitis (AD) are strongly associated with an impairment of the epithelial barrier, in which tight junctions and/or filaggrin expression can be defective. Skin barrier assessment shows potential to be clinically useful for prediction of disease development, improved and earlier diagnosis, lesion follow‐up, and therapy evaluation. This study aimed to establish a method to directly assess the in vivo status of epithelial barrier using electrical impedance spectroscopy (EIS). Methods: Thirty‐six patients with AD were followed during their 3‐week hospitalization and compared with 28 controls. EIS and transepidermal water loss (TEWL) were measured in lesional and non‐lesional skin. Targeted proteomics by proximity extension assay in serum and whole‐genome sequence were performed. Results: Electrical impedance spectroscopy was able to assess epithelial barrier integrity, differentiate between patients and controls without AD, and characterize lesional and non‐lesional skin of patients. It showed a significant negative correlation with TEWL, but a higher sensitivity to discriminate non‐lesional atopic skin from controls. During hospitalization, lesions reported a significant increase in EIS that correlated with healing, decreased SCORAD and itch scores. Additionally, EIS showed a significant inverse correlation with serum biomarkers associated with inflammatory pathways that may affect the epithelial barrier, particularly chemokines such as CCL13, CCL3, CCL7, and CXCL8 and other cytokines, such as IRAK1, IRAK4, and FG2, which were significantly high at admission. Furthermore, filaggrin copy numbers significantly correlated with EIS on non‐lesional skin of patients. Conclusions: Electrical impedance spectroscopy can be a useful tool to detect skin barrier dysfunction in vivo, valuable for the assessment of AD severity, progression, and therapy efficacy. Abstract : Electrical impedance spectroscopy differentiates between AD patients and controls. EIS can characterize lesional and non‐lesional skin of patients. During hospitalization, lesions showed a significant increase in EIS that correlated with healing. EIS scores showed a significant inverse correlation with serum biomarkers associated with inflammatory response, particularly chemokines such as CCL13, CCL3, CCL7, and CXCL8 and other molecules such as IRAK1, IRAK4, and FG2. Abbreviations: AD, atopic dermatitis; CCL, C‐C motif chemokine ligand; CXCL, C‐X‐C motif chemokine ligand; IRAK, interleukin 1 receptor associated kinase; FG2, fibroblast growth factor 2; EIS, electrical impedance spectroscopy; EIS score, the score given to a measurement by the artificial intelligence model based on EIS measurements